Robots, Disability, and Good Human Life - Carnevale, Antonio (Disability Studies Quarterly, 2015)
In this paper, I want to show the role that emerging robotic technologies could play in the future in daily life of disabled people. When I talk about disability, I mean any temporary or permanent limitation due to a chronic disease and deficit, as well as, socially disadvantaged conditions, which imply functional and emotional restrictions experienced at any age. All these limitations can be characterized by a specific mental and physical impairment or, more often, by a cluster of medical impairments and social barriers. To this end, the academic literature has generally differentiated between two disability models: 'medical' versus 'social'. The main attempt of this paper consists into showing how the development of robotic technologies — particularly in assistive and healthcare fields — could allow us to go beyond this outdated dichotomy, contributing to create new philosophical premises to rethink the universality of the human condition, that is, the sense of what we intend for 'good human life'.